Pengaruh Dukungan Sosial dan Harapan terhadap Resiliensi Anak Didik LAPAS Kelas IIA SAlemba - Sella Rizkina (JURNAL RAUDHAH, 2018)
This study was conducted to determine the effect of social support and expectation on the resilience of class IIA prison students. The authors theorized that social support, hope, and demographic variables consisting of education and prison terms had an effect on the resilience of the LAPAS students. This study uses quantitative approach with multiple regression analysis with a sample of 170 students Class IIA Salemba taken with non-probability sampling technique. CFA (Confirmatory Factor Analysis) is used to test the measuring tool and Multiple Regression Analysis is used to test the research hypothesis. All of these techniques, researchers use software SPSS 18.0 and LISREL 8.70. The conclusion of this study shows that there is a significant influence of social support and expectation on resilience with R-Square of 0.108, meaning that the variant proportion of resilience is explained by all independent variables of 10.8%, and 89.2% influenced by other variables. Key word : social support, hope, resilience, student of prision